Guanidium-assisted crystallization engineering for highly efficient CsPbI3 solar cells. Issue 21 (19th May 2022) - Wang, Shuo; Xu, Youkui; Wang, Qian; Zhou, Xufeng; Li, ZhenHua; Wang, Meng; Lei, Yutian; Zhang, Hong; Wang, Haoxu; Jin, Zhiwen
Abstract : This work mainly focuses on utilizing GA + to reduce non-radiative recombination in CsPbI3 by inhibiting the formation of iodine vacancies and passivating incompatible iodide, and the champion PCE was demonstrated to be 19.05% with a V OC of 1.14 V. Abstract : Iodine vacancies and uncoordinated iodide ions of CsPbI3 films are mainly responsible for nonradiative recombination. Here, we report a composition-engineering passivation method that through guanidium (GA + ) and I − forms strong hydrogen bonds to passivate iodine vacancies and reduce defects. Both experimental and theoretical results confirmed strong chemical interactions between GA + and uncoordinated I − in the GA x Cs1− x PbI3 bulk or at the grain boundary. Moreover, GA + doping could slow down the crystallization speed of perovskite films during the deposition process. As a result, we observed GA + modified films with much lower defect density, larger grain size, and better carrier extraction and transportation. Upon GA + passivation, the power conversion efficiency (PCE) is boosted from 18.01% to 19.05%, with open-circuit voltage ( V OC ) enhancement from 1.08 V to 1.14 V.